Science-Fiction et Empire - Istvan Csicsery-Ronay (Jr.) (ReS Futurae)
This essay makes a preliminary attempt to construct a cognitive map of sf as a creature of imperialism and inspired by a world-view of technoscientific Empire. The dominant historical sf cultures are those that attempted imperialist projects : US, UK, Russia, France, Germany, Japan. The conditions for sf’s emergence are established by imperialism and the role of technology, both in colonial conquest and political administration. The essay also argues that sf is imbued with the myth of Empire as a global technoscientific regime. Sf has an implied world-model, captured in aspects of Michael Hardt and Antonio Negri’s Emnpire, which is treated as a quasi-sf text and a geopolitical myth, rather than a work of political analysis.